BANKING REGULATIONS AS INSTRUMENTS FOR REGULATING NATIONAL ECONOMIC ACTIVITIES: A COMPREHENSIVE LITERATURE REVIEW OF THE ROLE OF BANK INDONESIA AND THE FINANCIAL SERVICES AUTHORITY IN ACHIEVING FINANCIAL STABILITY, SUSTAINABLE ECONOMIC GROWTH, AND MODERN PAYMENT SYSTEM INTEGRATION - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This study examines banking regulations as an instrument for regulating national economic activities through the complementary roles of Bank Indonesia (BI) and the Financial Services Authority (OJK) in achieving financial stability, sustainable economic growth, and modern payment system integration. Using a normative-descriptive literature review approach, the analysis focuses on the evolution of macroprudential-microprudential supervision after the 1998 crisis, the implementation of Basel III, the Sustainable Finance Roadmap, and BI-FAST and QRIS innovations that promote digital financial inclusion. The findings confirm that the synergy between BI and OJK through the Financial System Stability Committee (KSSK) has succeeded in balancing systemic stability with productive credit intermediation, green banking, and national payment transformation. The study recommends harmonising adaptive regulations, strengthening suptech, and accelerating sustainable taxonomy to address global disruption and Indonesia's 2045 economic vision.